Exploring actual and perceived levels of physical activity intensity during virtual reality active games - Naugle, Keith E.; Cervantes, Xzaliya A.; Boone, Carolyn L.; Wind, Brandon; Naugle, Kelly M. (Frontiers in Sports and Active Living, 2024)
Background Research suggests that engaging in active virtual reality (VR) video games can elicit light to moderate levels of physical activity (PA), making it a novel and fun mode of exercise. Further research is needed to understand the influence of VR on perceptions of exertion and enjoyment during PA. Objective The objectives of this study are (1) to compare actual and perceived exertion within and between active VR games with varying levels of difficulty and (2) to determine how playing active VR games influences PA enjoyment during gameplay. Methods A total of 18 participants completed four separate study sessions, during which they engaged in either a 15-min bout of traditional exercise (stationary cycling) or played one VR game. Heart rate (HR) and ratings of perceived exertion (RPE) using the Borg CR10 scale were assessed during VR gameplay and cycling. Enjoyment was measured after gameplay. VR games included playing Holopoint at level 2 and level 3 and Hot Squat. Repeated measures ANOVAs were used to examine (1) changes in HR and RPE across time within games and (2) differences in actual and perceived levels of intensity and enjoyment between games. Bivariate correlations examined the relationship between the degree of change in actual intensity and the degree of change in perceived intensity during each VR game and cycling. Results The analyses revealed that RPE and HR significantly increased from baseline during each condition and generally increased across the 15-min of gameplay. Hot Squat and cycling elicited a significantly higher percentage of heart rate reserve (%HRR) than Holopoint at levels 2 and 3. Holopoint level 3 elicited a higher %HRR than Holopoint level 2. The participants reported greater average and max RPE during Hot Squat and cycling compared with Holopoint at levels 2 and 3. The correlations revealed a significant positive correlation between the degree of change in HR and RPE for cycling, but no significant correlations were observed for any of the VR conditions. The physical activity during Holopoint at both levels was rated as more enjoyable than Hot Squat and cycling. Conclusion Our data support the notion that VR has the potential to alter individuals’ perceptions of exertion during PA and, in particular, may reduce their awareness of increases in actual exertion.